(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article examines innovative approaches to developing professional fitness competencies among future physical education teachers in the context of modern pedagogical transformation. It emphasizes that preparing qualified specialists capable of effectively organizing physical education processes requires not only physical readiness but also methodological, technological, and communicative competencies. The study highlights the integration of digital tools, simulation technologies, and interactive learning environments as key innovations that enhance students’ engagement and self-directed learning. The methodological basis of the research is grounded in competency-based, activity-based, and digital pedagogical approaches that focus on practical application and professional reflection. The results indicate that innovative teaching methods, such as blended learning, gamification, and virtual simulations, significantly contribute to improving students’ physical and professional competencies. The study also underlines the importance of interdisciplinary connections and health-oriented strategies that support the holistic development of future teachers. It concludes that innovation-driven physical education programs are essential for forming competent, adaptive, and reflective professionals capable of promoting health culture and physical literacy in educational institutions.